Determination of Diabetes and Dyslipidemia Goals in the Management of Diabetes - Jain, Rajesh; Olejas, Susanne; Davey, Sanjeev; Jain, Rachna; Shoghli, Reza; Iqbal, Mohammad; Tafti, Seyed Hoseyn Ahmadi; hosseini, Siyamak Jalal (New Frontiers in Medicine and Medical Research Vol. 14, 2021)
Diabetes Type I and Type II are at Increased Risk for early atherosclerotic CVD, i.e., CHD and PAD [1]; and It is known to us that Glucose control improves TG Level and Cholesterol-lowering has favorable effects on CVD outcomes in T1DM & T2 DM. The primary manifestation of dyslipidemia is the elevation of the total serum cholesterol, low-density lipoprotein (LDL) cholesterol, and triglyceride concentrations, and lower the high-density lipoprotein (HDL) cholesterol.